Investigating the Effects of Reducing Pathogen Levels in Cow Dung as an Organic Fertilizer Feedstock (Journal of Pure and Applied Sciences (Science Forum), 2024)
Organic fertilizer plays a pivotal role in sustainable agriculture, offering an ecofriendly alternative to inorganic fertilizers with their adverse long-term effects on soil health and environmental balance. However, the presence of pathogens in organic waste, such as cow dung, poses significant challenges to composting efficiency, soil stability, and end-user health. Despite its importance, previous studies have often overlooked the necessity of assessing pathogen levels in selected feedstocks, thereby hindering the optimization of composting processes. This study addresses this gap by focusing on pre-treating cow dung as a feedstock for fertilizer formulation to reduce pathogen levels. Chemical oxygen demand (COD) and total solid (TS) analyses were conducted on both untreated and treated samples, following ASTM standards D6238 and D5231, respectively. Results showed a substantial reduction in COD from an initial value of 293.98 mg/L to 27.02 mg/L and degradation of TS from 303.78 mg/L to 53.74 mg/L, indicating efficient pathogen reduction. Additionally, the volatile solid (VS) removal efficiency during pretreatment was found to be 80.1 %. It is therefore concluded that, the treated cow dung to mitigate pathogen levels proved to be suitable for use as feedstock in organic fertilizer production. This is evidence from the significant reductions in COD, TS, and VS concentrations by 90.8 %, 82.3 %, and 80.1 % respectively.